Oncologic significance of para-aortic lymph node and inferior mesenteric lymph node metastasis in sigmoid and rectal adenocarcinoma. Issue 11 (November 2017) - Lee, Seung Hyung; Lee, Jong Lyul; Kim, Chan Wook; Lee, Han IL.; Yu, Chang Sik; Kim, Jin Cheon
Abstract: Background: Recurrence patterns or survival in colorectal cancer patients might differ according to inferior mesenteric lymph node (IMLN) metastasis. However, few studies have compared para-aortic lymph node (PALN) metastasis and IMLN metastasis. The aim of the current study is to identify survival and recurrence patterns in patients with sigmoid colon and rectal adenocarcinoma with either PALN or IMLN metastasis and to evaluate the prognostic significance of PALN and IMLN metastasis. Methods: A retrospective study involving 3076 patients with stage III and IV sigmoid and rectal cancer, who underwent curative surgery between January 2000 and December 2009, was performed. Clinicopathologic features, recurrence patterns, and survival outcomes of 27 patients with PALN metastasis were compared with those of 47 patients with IMLN metastasis. Patients with both IMLN and PALN metastasis were included in the PALN+ group. Results: After curative resection, there was no significant difference in the 5-year disease-free and overall survival rates between the PALN+ and IMLN+ groups (27.5% vs . 29.8%, p = 0.24, and 37% vs . 39.2%, p = 0.19, respectively). Furthermore, there were no significant differences in recurrence rate (PALN+ group, 70.4%; and IMLN+ group, 63.8%; p = 0.69) or recurrence patterns. Conclusions: The results suggest that IMLN metastasis, similar to PALN metastasis, is associated with adverse oncologic outcomes and has prognostic significance. Therefore, it is preferable that IMLN metastasis should be considered under the category of systemic metastasis (M1).